2019
DOI: 10.1039/c9tb00019d
|View full text |Cite
|
Sign up to set email alerts
|

Boronic acid-functionalized molybdenum disulfide quantum dots for the ultrasensitive analysis of dopamine based on synergistic quenching effects from IFE and aggregation

Abstract: Boronic acid-functionalized molybdenum disulfide quantum dots (B-MoS2 QDs) were prepared for application as a rapid and sensitive platform for the quantitative analysis of dopamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…We suggest that PEI polymers not only suppress the aggregation of the FL-MnO 2 NSs and QDs but also replace adsorbed water molecules on the surface of the FL-MnO 2 NSs and QDs through the formation of hydrogen bonding. The following findings strengthen our assumption: (1) Guo et al reported that the self-aggregation of boric acid-functionalized MoS 2 QDs triggered their fluorescence quenching and (2) Varghese et al disclosed that the adsorbed water molecules efficiently quenched the fluorescence of single-layered MoS 2 nanosheets due to the stretching vibration of O–H bonds . The pH, temperature, and salt stability of the PEI-FL-MnO 2 NSs and QDs were evaluated by monitoring their maximum fluorescence intensity.…”
Section: Resultssupporting
confidence: 74%
“…We suggest that PEI polymers not only suppress the aggregation of the FL-MnO 2 NSs and QDs but also replace adsorbed water molecules on the surface of the FL-MnO 2 NSs and QDs through the formation of hydrogen bonding. The following findings strengthen our assumption: (1) Guo et al reported that the self-aggregation of boric acid-functionalized MoS 2 QDs triggered their fluorescence quenching and (2) Varghese et al disclosed that the adsorbed water molecules efficiently quenched the fluorescence of single-layered MoS 2 nanosheets due to the stretching vibration of O–H bonds . The pH, temperature, and salt stability of the PEI-FL-MnO 2 NSs and QDs were evaluated by monitoring their maximum fluorescence intensity.…”
Section: Resultssupporting
confidence: 74%
“…24 As shown in Figure 1D, the hydrodynamic diameter of g-C 3 N 4 QDs is 32.4 nm, which is nearly 10 times larger than that observed using TEM, demonstrating that there have many water molecules absorbed on the surface of g-C 3 N 4 QDs. 27 These results indicate that the g-C 3 N 4 QDs with excellent water solubility are synthesized successfully through a simple methylamine-assisted hydrothermal method for bulk g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 62%
“…After bulk g-C 3 N 4 is subjected to the methylamine-assisted hydrothermal method, the prepared g-C 3 N 4 QDs are found to be uniformly spotty, with a thickness of around 3.58 nm, indicating that the methylamine can react with distilled water to generate methyl alcohol and ammonia gas, which enters into the interlayer-stacking structure of C–N layers and further exfoliate bulk g-C 3 N 4 to form g-C 3 N 4 QDs . As shown in Figure D, the hydrodynamic diameter of g-C 3 N 4 QDs is 32.4 nm, which is nearly 10 times larger than that observed using TEM, demonstrating that there have many water molecules absorbed on the surface of g-C 3 N 4 QDs . These results indicate that the g-C 3 N 4 QDs with excellent water solubility are synthesized successfully through a simple methylamine-assisted hydrothermal method for bulk g-C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with their 2D and one dimensional (1D) counterparts, zero dimensional (0D) MoS 2 clusters possess tunable energy levels, more active edges, and larger surface-area-to-volume ratios, which give them fascinating properties. This makes them promising candidates for application in fields such as optoelectronics [14,15], electrochemical technology [16,17], biology [18], catalysis [19] and so forth [20][21][22]. Jaramillo et al [23] pointed out that 2D TMDs are hydrogen evolution reaction (HER) active because of their highly active edges, which makes them potential candidates for electrocatalytic hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%